[WITHDRAWN] The importance of increasing cigarette prices on National Health Insurance financing in Indonesia - Renny Nurhasana; Risky Kusuma Hartono; Faizal Rahmanto Moeis; Suci Puspita Ratih (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Indonesia faces the combined challenges of a high prevalence of active smokers and an increased financial burden of smoking-related Non-Communicable Diseases (NCDs) on National Health Insurance (NHI). This study aims to assess the importance of increasing cigarette prices for NHI funding. It was a cross-sectional study conducted through a phone survey. The survey was administered to 1,000 respondents aged 18 and over from various telecommunications operators in Indonesia. We performed the multivariate analysis and the framework of the importance of increasing cigarette prices for funding NHI. The result shows that the majority of the public supports the increase of cigarette price for funding NHI except for active smokers at Odds Ratio=0.529. The importance of increasing cigarette prices for funding NHI is supported by society, able to reduce the prevalence of active smokers, and it raises the government’s tax income. With the current strong public support, cigarette prices should be increased which will then be tagged to fund the NHI consistently. This is also seen as a means to compensate the high NCD-related claims of the NHI which are caused by smoking behavior.JEL Classification  H51; I13; I18